2019
DOI: 10.1186/s13229-019-0273-5
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability and reproducibility of functional connectivity in autism

Abstract: Background Autism is hypothesized to represent a disorder of brain connectivity, yet patterns of atypical functional connectivity show marked heterogeneity across individuals. Methods We used a large multi-site dataset comprised of a heterogeneous population of individuals with autism and typically developing individuals to compare a number of resting-state functional connectivity features of autism. These features were also tested in a single site sample that utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 66 publications
(78 reference statements)
7
51
1
Order By: Relevance
“…We should mention, however, that although there are different ways of dividing and grouping the data, these approaches mostly still fundamentally rest on the ability to accurately and reliably measure edge‐level differences in ASD (e.g., Yahata et al, ; see fig. 16a in King et al, ). For example, more complex statistical constructs that can be used to compare brain organization between groups (e.g., graph theoretic network measures; He et al, ; Rubinov & Sporns, ) fundamentally must build upon reliable and replicable measurement of connectomes.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We should mention, however, that although there are different ways of dividing and grouping the data, these approaches mostly still fundamentally rest on the ability to accurately and reliably measure edge‐level differences in ASD (e.g., Yahata et al, ; see fig. 16a in King et al, ). For example, more complex statistical constructs that can be used to compare brain organization between groups (e.g., graph theoretic network measures; He et al, ; Rubinov & Sporns, ) fundamentally must build upon reliable and replicable measurement of connectomes.…”
Section: Discussionmentioning
confidence: 96%
“…Holiga et al () recently found replicable results regarding functional connectivity in ASD across four very large datasets that also included ABIDE data. However, another recent study by King et al () assessed a number of different measures of functional connectivity in ASD and found weak evidence of generalizability across sites. Other studies have used machine learning approaches to generalize to independently acquired datasets (e.g., Abraham et al, ; Yahata et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations